Blocking a chemical communication between Trichoplax organisms leads to their disorderly movement. Issue 4 (3rd July 2020) - Kuznetsov, A. V.; Halaimova, A. V.; Ufimtseva, M. A.; Chelebieva, E. S.
ABSTRACT: We described an 'expansion' phenomenon of the Trichoplax sp. H2. The animals were transferred from algal mats to a Petri dish without food with the subsequent passage into the similar Petri dish. The animals' motion and receding into the distance at the new place was modelled by the increasing spacing between individuals/objects. A collective behaviour of trichoplaxes was disrupted by the addition of 0.01% Bovine Serum Albumin (BSA), which assumedly blocked an interaction of signalling molecules with receptors. BSA-treated trichoplaxes demonstrated the stochastic motion that is in a good agreement with the model of independent random particles. GRAPHICAL ABSTRACT: